Analisis Bauran Pemasaran Sayuran pada Ritel Hypermart Mal Bali Galeria - MARCFASU, BATRISYIA; SURYAWARDANI, I.G.A. OKA; ANGGRENI, I.G.A.A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Marketing Mix Analysis of Vegetables at Hypermart Mal Bali Galeria Retail Marketing mix strategy consists of product, price, place, and promotion are needed to increase the company's competitiveness of the Hypermart Mall Bali Galeria. This is due to the low sales of vegetable products compared to other fresh products. This study aims to analyze the implementation of the marketing mix and analyze the vegetable marketing mix strategy carried out by the Hypermart Mall Bali Galeria retail. This research was conducted at the Hypermart Mall Bali Galeria Retail, South Kuta. The data used in this study are primary data and secondary data with the informant interview, observation, and literature study methods. The data analysis technique was carried out qualitatively by identifying the company's internal and external factors, IFAS, EFAS, IE, and SWOT matrices to formulate alternative strategies for company development. The results showed that the marketing mix variables had been implemented properly and met the parameters and the results of the IE Matrix showed the company was in cell V which was included in the hold and maintain strategy category or maintain and continue the efforts that have been made by Hypermart Mal Bali Galeria with a focus on market penetration and product development. This shows that Hypemart Mal Bali Galeria can maintain the company's strategy and the quality of the products offered as well as expand the promotion of vegetable products through social media and make innovations regarding vegetable product packaging that aren’t use a lot of plastic by replacing it with environmentally friendly paper wrap pers.